Correlations of health literacy with individuals’ understanding and use of medications in Southern Taiwan - Chen Pin-Tzu; Chen Min-Li; Chang Li-Chun; Kuo Chin-Ho; Kuan Yu-Hsiang (Open Medicine)
Investigated the relationship between health literacy and treatment adherence and compliance due to incorrect medication use resulting from low health literacy in southern Taiwan.